If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6y + (4y + 3) = 0 Reorder the terms: 6y + (3 + 4y) = 0 Remove parenthesis around (3 + 4y) 6y + 3 + 4y = 0 Reorder the terms: 3 + 6y + 4y = 0 Combine like terms: 6y + 4y = 10y 3 + 10y = 0 Solving 3 + 10y = 0 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 10y = 0 + -3 Combine like terms: 3 + -3 = 0 0 + 10y = 0 + -3 10y = 0 + -3 Combine like terms: 0 + -3 = -3 10y = -3 Divide each side by '10'. y = -0.3 Simplifying y = -0.3
| 126=14x | | -5(1-3x)=-80 | | 9/5+3/5x=29/10+7/2x+1/2 | | 10-3n=n+4 | | 18+(x-1*4)=42 | | 12/5w+7=31-3/5w | | 4x-4+3=25 | | -6+2(x-6)=-36 | | 5x+8=-x+26 | | 1*4x+5+1*4x-5=2 | | (4x+3)+7x=16x-1 | | 8+7x-6x=11 | | -5*x-2-5*x+6=-3 | | 2x+9-13=-5 | | 6x+2=3x+26 | | 85=5(2+4z) | | 9=n/3+6 | | -7x-3x+7-2=-8x-8 | | 6y+6=3y-18 | | 11b-4=29 | | -3+5y=2y+3(y-1) | | 8x-4*4+9x+1*2=-7 | | -4x-5=-2x-1 | | 13+3m=-15 | | 116-4=29 | | 0.5h+.333333333(h-6)=.83h+2 | | -.75x-.25(2+7x)=-4.5+.50x | | -2=-7+x/5 | | 2y-6-y=1 | | 2+1/3t | | 9x=7-2x | | penis=dick |